Hoax News As An Ethical Violation Impact Of Information Technology Advances - Hasan, Ibnu; sokid, sokid (Ann Publisher, 2024)
The increasingly rapid development of technology must also be accompanied by the mindset of social network users to have harmony when facing changing times. Rephrase: Adjust the reception and dissemination of information using technology according to reality. It aims to describe the phenomenon of fake news (hoax) on social networks and online media and how to prevent fake news (hoax). It is used to visualize and describe data and facts about hoaxes and their spread through social media or online media. The study results show that easy and cheap technological advances are determining factors for information accessibility. Besides that, social media activists must also be more imaginative in utilizing information, especially an educated understanding of the media, which is often considered a source of truth, as well as the importance of the government's role in controlling the spread of fake news (hoax) that determines political decisions. Legal policies are regulated in the ITE Law.